Rindu Kembali Ke Baitullah: Sejarah Haji Asia Tenggara - Dadi Darmadi (Studia Islamika, 2018)
Eric Tagliacozzo, 2013. The Longest Journey: Southeast Asians and the Pilgrimage to Mecca. Oxford and New York: Oxford University Press.For many Muslims in Southeast Asia, the Hajj is not only an important spiritual experience but also a unique and very interesting story to tell. In this book, Eric Tagliacozzo painstakingly delivers the story of Hajj in Southeast Asia, where in the last five centuries, the Hajjis from Southeast Asian region have gone to Mecca to perform mandatory worship to perfect their religion. The longue duree approach that he uses not only enable him to unveil the reasons why millions of Southeast Asian Muslims have embarked on pilgrimage since the 15th CE, but also how the Hajj played great political and economic roles during the pre- and post-colonial periods up to this day, when the Hajj is increasingly complicated but, thanks to the advance of technology, it has become more affordable for many. Enriched with a sharp analysis of history and anthropology, the book is undoubtedly a very important contribution to the increased interest in the study of Hajj in the Malay-Indonesian archipelago and Southeast Asia.DOI: 10.15408/sdi.v25i1.7839